Editorial [Hot Topic: T-Type Calcium Channels in Health and Disease (Guest Editor: Slobodan M. Todorovic)] - Todorovic, Slobodan M. (CNS & Neurological Disorders - Drug Targets, 2006)
Voltage-gated calcium (Ca2+) channels are heteromeric complexes found in the plasma membrane of virtually all cell types and show a high level of electrophysiological and pharmacological diversity. On the basis of the membrane potential at which they activate, these channels are subdivided into high voltage-activated (HVA) and low voltage-activated (LVA) or transient (Ttype) Ca2+ channels. These channels in nerve tissue play a central role in controlling cell excitability and neurotransmitter release. Whereas it has been known that HVA-type Ca2+ currents arise from multiple forms of Ca2+ channels with distinct pharmacological properties, the extent to which T-type Ca2+ current arises from multiple Ca2+ channel subtypes became clear more recently. Recent cloning of 1 subunits of T-type channels has revealed the existence of at least three subtypes named G (CaV3.1), H (CaV3.2) and I (CaV3.3) that are likely to contribute to the heterogeneity of T-type Ca2+ currents observed in native cells. Although T-type currents are relatively easy to study in isolation from other Ca2+ current components by virtue of their unique biophysical properties such as activation, inactivation and deactivation, pharmacological tools for identification and investigation of T-type currents are limited. However, recent cloning of T-type calcium channels and development of more selective blockers of T-type channels allowed better understanding of the roles of these channels in control of the variety of physiological functions in the central nervous system (CNS) and peripheral tissues. Thus, the major roles for the T-type channels in neurons include promotion of Ca2+-dependent burst firing, low-amplitude intrinsic neuronal oscillations, promotion of Ca2+ entry and boosting of synaptic signals. Furthermore, T-type currents in the thalamus appear to play a role in seizure susceptibility and initiation and T-type channels in peripheral sensory neurons play an important role in boosting of pain signals. In this review, we summarize the most recent evidence of the multiple roles of T-type calcium channels in neurons and their role in various physiological and pathological conditions such as pain disorders, absence seizure and sleep disorders. Better definition of the pharmacological properties of different T-type current variants in these cells is of major importance in understanding the physiological role of these currents and their participation in the effects of clinical drugs. Furthermore, future functional studies and development of selective blockers of T-type channels will allow better understanding of their role in pathological processes of the central and peripheral nervous system as well.